TRANSFORMATIONAL TRANSFORMATIONAL LEADERSHI STYLE CAN MODERATE THE INFLUENCE OF WORK MOTIVATION VARIABLES ON EMPLOYEE PERFORMANCE - Adi Soeprapto; A. Idun Suwarna; Albert; Alita Misila Salasabila; Riki Adriant (Adisam Publisher, 2025)
This research is a quantitative study with an explanatory approach, namely an approach that makes a number of previous studies the main strength in proving each hypothesis used in this article. Each hypothesis is proven through gradual testing, starting with a validity test as the first stage, a reliability test as the second stage, and path efficiency as the last stage ; The data used in this article is primary data that researchers obtained from PO Sinar Jaya employees spread throughout Indonesia as many as 300 employees